Development of piezo–electric actuators and sensors for electronically controlled suspension. (4th August 2014) - Fukami, A.; Yano, M.; Tokuda, H.; Kizu, R.
New piezo–electric actuators and sensors applied to an electronically controlled suspension system have been developed. The material design of the actuator focuses on actuator's output, which is the product of displacement and generated force. A sensor has also been developed to detect the road surface conditions. Both the actuator and sensor are installed in the piston rod of a shock absorber. The sensor detects vertical irregularities on the road surface with high sensitivity and rapid response. The damping force generated by the shock absorber is controlled by the actuator with rapid response.